Low energy availability risk is associated with anxiety in female collegiate athletes - Scheid, J. L.; Basile, S.; West, S. L. (Sports, 2024)
This study investigated the association between the risk of low energy availability, disordered eating, and anxiety in collegiate female athletes. Female athletes (n = 115) completed questionnaires that assessed disordered eating (Disordered Eating Screen for Athletes, DESA-6; and the Eating Disorder Examination Questionnaire Short, EDE-QS), anxiety (Generalized Anxiety Disorder-7) and the risk of low energy availability (Low Energy Availability in Females Questionnaire; LEAF-Q). The athletes were 19.9 ± 0.1 years old and presented with no anxiety (14.8%), mild (33.0%), moderate (24.3%), and severe (27.8%) anxiety. The EDE-QS scores revealed that 22.6% of the participants had a high risk of an eating disorder, while the DESA-6 scores revealed that 31.3% of the participants scored positive for a risk of disordered eating. The LEAF-Q total scores revealed that 68.7% of the participants were at risk of low energy availability. Increased GAD-7 scores were associated (p < 0.001) with measures of disordered eating (EDE-QS and DESA-6) and the risk of low energy availability (LEAF-Q total score). Non-parametric partial correlations demonstrated that anxiety (increased GAD-7 scores) correlated with the risk of low energy availability (increased LEAF-Q total scores) while controlling for eating disorder scores (EDE-QS) (r (112) = 0.353, p < 0.001), or while controlling for the risk of disordered eating (DESA-6 scores) (r (112) = 0.349, p < 0.001). In female collegiate athletes, both disordered eating and the risk of low energy availability were positively associated with increased anxiety.